1991
DOI: 10.1111/j.1349-7006.1991.tb01924.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Expression of Blood Group–related Antigens in Uterine Endometrial Cancers

Abstract: The expression of A, B, and H group antigens, Lewis group antigens (Lewisa, Lewisb, Lewisx, and Lewisy), and Lc4 and nLc4 antigens, the precursor antigens of both groups, was examined immunohistochemically with monoclonal antibodies in 9 normal endometria, 6 endometrial hyperplasias, and 31 endometrial cancers. 1) A, B and/or H antigens were detected in endometrial cancers at an incidence of 51.6%, while no distinct localization of these antigens was observed in normal endometria. H antigen, the precursor of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…In addition, we previously analyzed the expression of carbohydrate chains in endometrial cancer, and found that the expression of type 1 carbohydrate chains predominates over type 2 carbohydrate chains. In particular, Lewis b carbohydrate chains are most specifically found in endometrial cancer [14]. Regarding the mechanism of expression of Lewis b carbohydrate chains by endometrial cancer, it has been suggested that a marked increase of ·-1,4-fucosyltransferase (FT) is more important compared with changes of ·-1,2FT and ·-1,3FT among the FT [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we previously analyzed the expression of carbohydrate chains in endometrial cancer, and found that the expression of type 1 carbohydrate chains predominates over type 2 carbohydrate chains. In particular, Lewis b carbohydrate chains are most specifically found in endometrial cancer [14]. Regarding the mechanism of expression of Lewis b carbohydrate chains by endometrial cancer, it has been suggested that a marked increase of ·-1,4-fucosyltransferase (FT) is more important compared with changes of ·-1,2FT and ·-1,3FT among the FT [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical staining was carried out by the avidin-biotin-complex method [14]. Tissue sections were incubated with an anti-ß-1,4GT monoclonal antibody (Konica, Tokyo) overnight at 4°C and subsequently treated with biotinylated horse antimouse IgG and avidin-biotin-complex reagent (Vector Laboratory, Burlingame, Calif.).…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher proportions of blood group A among patients with some malignant tumors has been shown [12,24,25]. The biological significance of blood group antigens as markers of progression in human tumors has been suggested in many investigations [26][27][28][29][30][31][32]. Among these blood group antigens, an excess of blood group A has frequently been reported among patients with cancer of the stomach [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrate antigen expressions have been proven to undergo qualitative and quantitative alterations during the normal menstrual cycle and a malignant transformation of the endometrium [1-3, Correspondence to: Masanori Yasuda, MD, Department of Pathology, Tokai University School of Medicine, Bohseidai, Isehara, Kanagawa 259-1193, Japan. [15][16][17][18]22]. Taking advantage of these findings, some investigators have attempted to synthesize monoclonal antibodies specific for endometrial adenocarcinomas (EMACs) [8,12,13].…”
Section: Introductionmentioning
confidence: 99%